Perception paysanne sur la fragmentation du paysage de la Forêt classée de l’Ouémé Supérieur au nord du Bénin - Kouagou Raoul Sambieni; Mireille Scholastique Toyi; Adi Mama (VertigO, 2015)
According to the failure of tropical forest landscapes various planning and the increasing fragmentation, it is urgent to find strategies for sustainable management of natural resources and biodiversity. This study analyzes local perceptions of the ecological quality of Upper Oueme forest reserve habitats landscape in northern Benin and main factors of its fragmentation. Data collected from 247 respondents by interviews and focus group were used to design answers’ frequency diagram follow by a Khi2 test on gender and corresponding factor analysis between socio-professional categories. Results show that according to populations, the level of degradation of Upper Oueme habitats forest reserve landscape is high to mean and the main factors of fragmentation are wood exploitation, bush fires and grazing. These results underline the necessity and the relevance of the study of local perceptions of the habitat quality of the forest landscapes to better guide management measures which should now be taken in a landscape approach.